2019
DOI: 10.1016/j.amepre.2018.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Videogames, Physical Activity, and Health: Wii Heart Fitness: A Randomized Clinical Trial

Abstract: Introduction: Adults who engage in regular physical activity have lower rates of morbidity and mortality than those who do not. Exercise videogames may offer an attractive, sustainable alternative or supplement to traditional modes of exercise. This study compared exercise videogames with standard exercise modalities for improving uptake and maintenance of moderate to vigorous physical activity, and health risk indices. Study design: A three-arm clinical RCT including 12 weeks of supervised laboratory-based mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
3
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 72 publications
0
25
3
6
Order By: Relevance
“…17 Studies with adult populations have shown similar results, in which AVG play leads to greater postintervention exercise behavior. 14 Possibly, this occurs because playing AVG, rather increasing the RRV of AVG, decreases the RRV of SVG, which then makes alternatives, such as TAP, more appealing. Alternately, this result may be largely due to postintervention decreases in Pmax AVG .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Studies with adult populations have shown similar results, in which AVG play leads to greater postintervention exercise behavior. 14 Possibly, this occurs because playing AVG, rather increasing the RRV of AVG, decreases the RRV of SVG, which then makes alternatives, such as TAP, more appealing. Alternately, this result may be largely due to postintervention decreases in Pmax AVG .…”
Section: Discussionmentioning
confidence: 99%
“…12 Studies of whether AVG play result in increased energy expenditure often show conflicting results, with some studies showing no increased energy expenditure over nonactive sedentary videogames (SVGs) 13 and others showing increased physical activity. 12,14 AVG energy expenditure appears to be particularly high in games facilitating lower body movements, such as running and kicking, 12,15 but typically lower than occurs in TAP. 16 Increased exposure to active play through AVG may promote incentive sensitization of AVG, TAP, or both; but this is not yet known.…”
Section: Introductionmentioning
confidence: 97%
“…De hecho, se la ha considerado como la pandemia del siglo XXI (7) . Al mismo tiempo, se considera uno de los principales problemas de salud pública, donde se requiere la puesta en marcha de enfoques multifacéticos que incluyan estrategias innovadoras para incorporar la AF en las rutinas diarias de las personas (8) .…”
Section: Introductionunclassified
“…Por otro lado, desde hace tiempo ha surgido una novedosa manera de practicar AF denominada videojuegos activos (VA) (10,11) . Se refiere a la puesta en marcha de ejercicios físicos con plena interacción con los videojuegos, en donde es preciso la realización de movimientos corporales sustanciales y esfuerzo para continuar jugando, permitiendo la realización de AF para aquellos individuos que quieran practicarla pero no cuentan con el tiempo para ello (8) , creyendo así que podría ser una forma de actividad para compartir y practicar en familia.…”
Section: Introductionunclassified
“…The exercise intensity plays an important role in an effective functional fitness training process and should be adapted to individual elders' physical conditions accordingly. Exercise videogames by using technologies of motion detection or gesture recognition for elders' functional fitness training (e.g., fall prevention) become an acceptable, attractive, and sustainable approach among elders (Bieryla & Dold, 2013;Bock et al, 2019;Ejupi, Gschwind, Valenzuela, Lord, & Delbaere, 2016;Vaziri et al, 2017;Williams et al, 2010).…”
Section: Introductionmentioning
confidence: 99%